2018
DOI: 10.1186/s40608-018-0219-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between gestational weight gain and rate of infancy weight gain in Hawai‘i and Puerto Rico WIC participants

Abstract: BackgroundExcessive gestational weight gain and rapid infancy weight gain (RIWG) are associated with increased susceptibility to childhood obesity. Since low-income and minority children are particularly at risk, investigation of the associations between gestational weight gain and rate of infancy weight gain may inform childhood obesity prevention. This study investigated the associations between gestational weight gain and rate of infancy weight gain during the first four to six months postpartum in particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This further emphasizes the need to specifically examine potentially modifiable risk factors leading to adverse birth outcomes in this population. Previous research among women in Puerto Rico has indicated that infants born to women with low and excessive GWG have decreased weight gain between 4 and 6 months compared to infants born to women with adequate weight gain during pregnancy [32]. Excessive GWG has also been associated with increased odds of hypertensive disorders during pregnancy in a predominantly Puerto Rician population [33].…”
Section: Discussionmentioning
confidence: 99%
“…This further emphasizes the need to specifically examine potentially modifiable risk factors leading to adverse birth outcomes in this population. Previous research among women in Puerto Rico has indicated that infants born to women with low and excessive GWG have decreased weight gain between 4 and 6 months compared to infants born to women with adequate weight gain during pregnancy [32]. Excessive GWG has also been associated with increased odds of hypertensive disorders during pregnancy in a predominantly Puerto Rician population [33].…”
Section: Discussionmentioning
confidence: 99%
“…Much of the literature is state or city specific or restricted by small sample sizes, and findings have been inconsistent. [15][16][17][18][19] For instance, there is little consensus in the literature regarding the efficacy of the breastfeeding education provided by the WIC program. A 2016 study of 743 individuals enrolled in WIC demonstrated no associations with breastfeeding at 3 months postpartum, contradicting previous studies which found negative associations.…”
Section: Study Aimsmentioning
confidence: 99%
“…Previous studies that assess the efficacy and impacts of the WIC program among pregnant women are limited. Much of the literature is state or city specific or restricted by small sample sizes, and findings have been inconsistent 15–19 . For instance, there is little consensus in the literature regarding the efficacy of the breastfeeding education provided by the WIC program.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, many studies did not include important covariates of infant weight gain and pubertal development, such as maternal gestational weight gain (GWG), prior livebirths, or childhood obesity [ 19 21 ]. Since infant catch-up growth is strongly associated with GWG [ 19 , 20 ] and childhood obesity [ 22 , 23 ], it is important to include these variables in the analysis. We addressed these limitations by conducting a prospective study using a large, racially/ethnically diverse cohort of girls from Northern California and comprehensive clinical data.…”
Section: Introductionmentioning
confidence: 99%